Casting light on energy efficiency: evidence on consumer inattention and imperfect information - Rodemeier, Matthias; Löschel, Andreas; Kube, Roland (Applied economics letters, 2017)
We investigate consumer inattention and imperfect information regarding the financial benefits of energy-efficient lighting using a randomized controlled trial with 1084 observations. Results suggest that subjects generally know about cost savings of light-emitting diode (LED) bulbs - the central lighting technology of the future - but largely underestimate the magnitude of these savings. As a result, stated willingness-to-pay for an LED bulb increases on average by 2.53€ through the provision of information on expected lifetime costs. Additional evidence hints at further consumer confusion about attribute differences between lighting technologies.